Eversion with four sutures: An easy, fast, and reliable technique for microvascular anastomosis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2001)
In this study, a microvascular anastomosing technique called eversion with four sutures is introduced. For microvascular anastomosis, this technique requires fish-mouth incisions at both vessel ends and the completion of four sutures. In 120 Wistar-Albino rats, 120 eversion and 120 conventional anastomoses were done in 240 femoral arteries. Each rat received both treatments. Operating time, bleeding time, number of sutures used, patency rates, and pseudoaneurysm formation were analyzed statistically; healing was evaluated with both light and electron microscopy. When compared with the conventional technique using nine sutures, the eversion with four sutures technique was found to be a faster and easier method of anastomosis and as reliable as the conventional technique. without compromising patency rates, bleeding time, or rates of pseudoaneurysm formation, anastomosis time and amount of suture material exposed to the lumen were significantly reduced when using this technique. In conclusion, the authors think that eversion with four sutures is a reliable alternative to the conventional suturing technique, especially for emergency cases that require multiple microvascular anastomoses.
Keywords: RATS